2010
DOI: 10.1002/ab.20351
|View full text |Cite
|
Sign up to set email alerts
|

Power of being present: the role of mindfulness on the relation between men's alcohol use and sexual aggression toward intimate partners

Abstract: The primary aim of this investigation was to examine the association between men's level of mindfulness and histories of alcohol consumption and sexual aggression toward intimate partners. Participants were 167 heterosexual drinking males who completed self-report measures of mindfulness, frequency and quantity of alcohol consumption during the past 12 months, and sexual aggression against intimate partners during the past 12 months. Results indicated that a history of consuming larger amounts when drinking wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 60 publications
(78 reference statements)
2
46
0
Order By: Relevance
“…Research has demonstrated that alcohol use and mindfulness interact to predict male perpetrated sexual aggression (Gallagher et al, 2010), and research could examine whether alcohol use, a robust correlate of dating violence perpetration, interacts with mindfulness to predict female aggression. Mindfulness has also been conceptualized by researchers in number of ways, including as a single facet, as including two facets, and five.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that alcohol use and mindfulness interact to predict male perpetrated sexual aggression (Gallagher et al, 2010), and research could examine whether alcohol use, a robust correlate of dating violence perpetration, interacts with mindfulness to predict female aggression. Mindfulness has also been conceptualized by researchers in number of ways, including as a single facet, as including two facets, and five.…”
Section: Discussionmentioning
confidence: 99%
“…Both of the above studies did not distinguish with whom the aggression was perpetrated against. Finally, Gallagher, Hudepohl, and Parrott (2010) found that increased mindfulness was negatively associated with sexual aggression perpetration against a dating partner within a sample of male college students. All of the above studies assessed mindfulness unidimensionally.…”
Section: Mindfulness and Aggressionmentioning
confidence: 92%
“…One means of accomplishing this is through mindfulness-based interventions, which could be used to boost selfreflection and outcome evaluation in ways that counteract myopia and reduce men's objectification of women. Supporting this possibility are correlational findings that heavy drinking is associated with sexual aggression only among men low in mindfulness (Gallagher et al 2010).…”
Section: Practice Implicationsmentioning
confidence: 98%
“…Meta-analytic reviews evidence smaller effect sizes of alcohol on aggression when participants are distracted (Bushman & Cooper, 1990). Cross-sectional studies suggest that heavy drinking is associated with IPV primarily among individuals who endorse dispositional tendencies in aggression-related cognitive biases (e.g., high hostility; Leonard & Blane, 1992) or who are susceptible to alcohol-related shifts in attention toward instigatory cues (e.g., low mindfulness; Gallagher, Hudepohl, & Parrott, 2010). To this end, prior research has demonstrated that individuals at risk for aggression show attentional biases toward aggression-relevant contextual stimuli (Eckhardt & Cohen, 1997; Smith & Waterman, 2004).…”
Section: Theoretical Considerationsmentioning
confidence: 99%